2010
DOI: 10.1002/acr.20257
|View full text |Cite
|
Sign up to set email alerts
|

Association of pruritus with quality of life and disability in systemic sclerosis

Abstract: Objective. To our knowledge, no studies have investigated the association of pruritus, which is present in almost half of patients with systemic sclerosis (SSc; scleroderma), with quality of life (QOL) and disability. The objective of this study was to investigate the association of pruritus with QOL and disability in SSc. Methods. We performed a cross-sectional, multicenter study of 578 SSc patients >1 year post-enrollment in the Canadian Scleroderma Research Group Registry. Patients reported whether they exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…28 Pruritus Pruritus, or itch, is common in SSc and is associated with HRQL, even after controlling for sociodemographic and other SSc symptom variables. 29,30 Overall, 43% of 959 patients with SSc from a Canadian registry reported pruritus on most days in the last month. 31 This rate was slightly higher, but not statistically significant, among patients with early SSc (<5 years since onset of non-Raynaud symptoms, 46%) versus those with longer disease duration (5 years, 41%).…”
Section: Continuedmentioning
confidence: 99%
“…28 Pruritus Pruritus, or itch, is common in SSc and is associated with HRQL, even after controlling for sociodemographic and other SSc symptom variables. 29,30 Overall, 43% of 959 patients with SSc from a Canadian registry reported pruritus on most days in the last month. 31 This rate was slightly higher, but not statistically significant, among patients with early SSc (<5 years since onset of non-Raynaud symptoms, 46%) versus those with longer disease duration (5 years, 41%).…”
Section: Continuedmentioning
confidence: 99%
“…Pruritic patients with systemic sclerosis had significantly worse mental and physical function and greater disability. In multivariate analyses controlling for demographic and disease variables, pruritus was independently associated with mental ( p ¼ 0.017) and physical function ( p ¼ 0.003) but not disability ( p ¼ 0.112) (El-Baalbaki et al 2010).…”
Section: Extracutaneous Diseasementioning
confidence: 99%
“…A cross-sectional study with patients affected by systemic sclerosis from Canada measured QoL according to the 36-Item Short Form Health Survey. Patients suffering from pruritus had a significantly greater negative impact on QoL than patients without pruritus [22]. A cross-sectional study in 13 European countries with 250 consecutive patients and 125 healthy controls demonstrated that patients reporting itch were more depressed than those without itch, had more anxiety and a larger impact on QoL measured by the DLQI [23].…”
Section: Discussionmentioning
confidence: 99%